THE INFLUENCE OF FINANCIAL STABILITY AND EXTERNAL PRESSURE ON FINANCIAL STATEMENT FRAUD - Leonard Pangaribuan; Rachmat Agus Santoso (Jurnal Scientia, 2023)
The purpose of this study is to collect empirical evidence regarding the effect of financial stability by ACHANGE proxy and external pressure by LEV proxy on financial statement fraud using the F-Score model. This study observes manufacturing businesses in basic and chemical industries listed on the Indonesia Stock Exchange for five years, from 2016 to 2020. This study includes a sample of 63 businesses. Purposive sampling was used as a sampling method. The research findings show that financial statement fraud is significantly influenced by financial stability and external pressure . The partial test results show that external pressure has a significant negative effect on financial statement fraud . Financial stability has no significant effect on financial statement fraud , but external pressure has a significant negative effect on financial statement fraud